Current Common Dilemmas in Colorectal Surgery (Springer International Publishing, 2018)
This text reviews the areas of colorectal surgery that are at the cutting edge of innovation, paradigm shift and controversy with regard to diagnosis, patient selection, treatment algorithm, and therapeutic approaches. From the impact of enhanced recovery protocols on traditional colorectal practices, to that of novel strategies merging endoscopic and surgical techniques, to recent paradigm shifts in the management of common colorectal disorders, this text provides readers with an update on current controversies and evolving treatment rationale in the management of common colorectal diseases. Current Common Dilemmas in Colorectal Surgery provides a guide for the current common dilemmas that caregivers encounter in their daily practice. It is of great utility to colorectal surgeons, surgical oncologists and general surgeons practicing colorectal surgery, senior residents in general surgery training or surgical oncology or colorectal fellowships, allied healthcare professionals involved in the care of patients with colorectal disease, pharma and biomedical technology industry with an interest in current care of patients with colorectal disease.